2008
DOI: 10.1111/j.1460-9568.2008.06324.x
|View full text |Cite
|
Sign up to set email alerts
|

A plateau potential mediated by the activation of extrasynaptic NMDA receptors in rat hippocampal CA1 pyramidal neurons

Abstract: Hippocampal pyramidal neurons express various extrasynaptic glutamate receptors. When glutamate spillover was facilitated by blocking glutamate uptake and fast synaptic transmission was blocked by antagonists of AMPA- and NMDA-type glutamate receptors and an ionotropic GABA receptor blocker, repetitive synaptic stimulation evoked a persistent membrane depolarization that consisted of an early Ca(2+)-independent component and a late Ca(2+)-dependent component. The early component, which we refer to as a plateau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
35
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 63 publications
2
35
0
Order By: Relevance
“…When mode 2 gating is down, LTCC activation during physiological stimuli will preferentially have excitatory effects, e.g., driving bursts and promoting EPSPs. However, during long-lasting depolarizing voltage shifts, e.g., those that are thought to occur in neurons under ischemic conditions (8) or under conditions promoting plateau potentials (12,20,38), the coupling of LTCCs to K Ca 2.x channels may be activated, potentially supporting the counteraction of excitotoxicity (39).…”
Section: Discussionmentioning
confidence: 98%
“…When mode 2 gating is down, LTCC activation during physiological stimuli will preferentially have excitatory effects, e.g., driving bursts and promoting EPSPs. However, during long-lasting depolarizing voltage shifts, e.g., those that are thought to occur in neurons under ischemic conditions (8) or under conditions promoting plateau potentials (12,20,38), the coupling of LTCCs to K Ca 2.x channels may be activated, potentially supporting the counteraction of excitotoxicity (39).…”
Section: Discussionmentioning
confidence: 98%
“…Receptor channels located outside the synaptic cleft may also contribute charge to dendritic spikes [5,[12][13][14]. Besides the afferent glutamatergic axons, glial processes may also release glutamate that contributes to the glutamate build up (glutamate threshold) required to bring a dendrite into an UP state, which in turn brings the cell body into an UP state [1,15].…”
Section: Introductionmentioning
confidence: 99%
“…This study is based on the hypothesis that both dendritic events, NMDA spikes and glutamate-mediated plateau potentials, are driven by five critical processes: (i) synchronous activation of spatially segregated presynaptic glutamatergic terminals [16], (ii) failure of nearby glial processes to clear the bulk of extracellular glutamate [5,12,13], (iii) stimulation of extrasynaptic NR2C/D receptors on spine necks and dendritic shafts by spilled-over glutamate [12,13,17,18], (iv) glutamatedependent release of adenosine from either neurons or glia, or both [19,20], and (v) activation of adenosine-sensitive dendritic K þ current, which imposes negative feedback on the amplitude and duration of dendritic depolarizations. The aforementioned five processes (i-v) synergistically contribute to the generation of local dendritic regenerative events.…”
Section: Introductionmentioning
confidence: 99%
“…Extrasynaptic NMDAR are activated following high-frequency stimulation and subsequent synaptic glutamate spillover and/or nonneuronal glutamate release. Previous reports suggest that tonic NMDAR-mediated currents activated by ambient endogenous glutamate levels elicit plateau potentials and enhanced neuronal excitability via increased excitatory input-output gain (Sah et al 1989;Suzuki et al 2008). However, other studies reported no significant effect of small-amplitude tonic NMDAR-mediated currents on neuronal excitability (Cavelier and Attwell 2005;Le Meur et al 2007).…”
Section: Discussionmentioning
confidence: 89%
“…Chronic use of these antagonists led to neuronal vacuolization, paradoxical seizure exacerbation, increased synaptic connectivity, and increased ionotropic glutamate receptor expression (Gould et al 1994;Ikonomidou et al 1999;Loscher 1998;Muir and Lees 1995;Olney et al 1989;Parsons et al 1999;Sveinbjornsdottir et al 1993;Wang and Bausch 2004). A number of newer NMDAR antagonists appear to reduce pathological overactivation while better maintaining the physiological NMDAR function required for normal brain function.…”
mentioning
confidence: 99%